2020
DOI: 10.1002/eng2.12159
|View full text |Cite
|
Sign up to set email alerts
|

Melting and viscous dissipation effect on upper‐convected Maxwell and Williamson nanofluid

Abstract: This article mainly addresses the influence of the viscous dissipation, melting, and chemical reaction on Williamson and Maxwell nanofluids over a stretching sheet embedded in porous media. The system of partial differential equations which is obtained by conservation principles, is transformed by means of an appropriate similarity transformation into a system of ordinary differential equations. The numerical results are obtained by employing the Keller box method. The impacts of different germane parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Among these models, existing literature shows little consideration has been made to the upper convected Maxwell (UCM) model, which is a sub‐arrangement of the rate‐type fluid. In 2020, Ibrahim and Negera 26 investigated the impact of chemical reaction, melting and viscous dissipation on Williamson and UCM nanofluids over an expanding sheet in porous medium. They showed that melting profoundly influences boundary layer velocity of Williamson nanofluid when contrasted with UCM nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Among these models, existing literature shows little consideration has been made to the upper convected Maxwell (UCM) model, which is a sub‐arrangement of the rate‐type fluid. In 2020, Ibrahim and Negera 26 investigated the impact of chemical reaction, melting and viscous dissipation on Williamson and UCM nanofluids over an expanding sheet in porous medium. They showed that melting profoundly influences boundary layer velocity of Williamson nanofluid when contrasted with UCM nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…It is a new major that is used in the aerospace industry. In addition, MHD is one of the methods that can influence heat and flow on a stretching sheet 1–5 . Naikoti Kishan et al 6 investigated MHD impact the warm exchange over a extending sheet rooted in a permeable medium with variable viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MHD is one of the methods that can influence heat and flow on a stretching sheet. [1][2][3][4][5] Naikoti Kishan et al 6 investigated MHD impact the warm exchange over a extending sheet rooted in a permeable medium with variable viscosity. Similarly, Stanford Shateyi et al 7 focused on the numerical investigation of three-dimensional MHD nanofluid stream over a extending sheet with convective boundary circumstances by means of a permeable medium..…”
Section: Introductionmentioning
confidence: 99%
“…In this paragraph other nonlinear models is discussed to know the importance of nonlinear problems in real life. Ibrahim et al [24] uses the Kellar box approach to discuss the effects of viscous dissipation, melting over a stretching sheet, a chemical reaction on williamson and maxwell nanofluids. Ajibade et al [25] used the DTM approach to study suction and injection on a vertical channel.…”
Section: Introductionmentioning
confidence: 99%